THE ROLE OF INNOVATIVE TECHNOLOGIES IN TEACHING PHONETIC EXERCISES IN THE PRIMARY CLASS - Ma’mura KENJAYEVA (Scholar Express Journal, 2023)
In this article, the role of using innovative technologies in the teaching of phonetic exercises is analyzed in a timely and qualitative manner. The data was collected using practical tests with students, as well as scientific articles and questionnaires.
Keywords: Classroom; phonics; exercise